Effectiveness of health promotion and public health interventions: Lessons from Latin American Cases (Colombia Medica, 2010)
The issue of evidence of effectiveness in public health and health promotion has occupied the attention of academics, technicians, and politicians who recognize not only its importance but the challenges that researchers must confront to obtain reliable and useful information to base public policy decisions and investment of resources. Despite the emergence of Latin American initiatives aimed at building the capacity to obtain such evidence of effectiveness, the practice is still incipient in the region and there are few relevant publications. This article is presented as a contribution and stimulus to further motivate the ongoing search for information and knowledge, concerning the relevance and scope of the practice of public health and health promotion to address adverse health conditions. For this purpose, a review of the literature was carried out, along with the compilation, documentation, and analysis of various cases of Latin American evaluations. From the product of this analysis, proposals are presented for strengthening the theoretical and evaluative practices in Latin America.